(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
In this article, the possible social activity of future teachers is studied. And their possible place in the socio-political life of society. Special attention is paid to the state youth policy. Also, the participation of students and youth of our country in the ongoing reforms was considered. These reforms are being systematically and purposefully carried out by the leadership of our country. They are aimed primarily at the future generation, their legal succession and responsibility to the memory of their ancestors. Future teachers should learn to take into account technological innovations, first of all, taking into account national and regional peculiarities. First of all, within the framework of their national traditions and religious tolerance.